PENGARUH PEMBERIAN GREEN TONIK DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL JAHE MERAH (ZINGIBER OFFICINALE ROSC.) PADA TANAH GAMBUT PEDALAMAN: THE EFFECT OF GREEN TONIC AND CHICKEN MANURE APLICATION ON THE GROWTH AND YIELDOF RED GINGER (ZINGIBER OFFICINALEROSC.) IN INLAND PEAT SOIL - Adji, Fengky Florante; Sirenden , Ruben Tintin; Darung , Untung; Chotimah , Hastin Ernawati Nur Chusnul (AgriPeat, 2024)
The objective of this study was conducted to find out the effects of giving leaf fertilizer green tonic and organic fertilizer on the growth and yield of red ginger. The experimental design used was a factorial Completely Randomized Design (CRD) with two treatment factors. The first factor is giving leaf fertilizer green tonic, which consisted of 4 levels of concentrations of 0, 4, 5, and 6 ml liter-1 of water, while the second factor is giving organic fertilizer is divided into 4 levels doses of 0, 10, 20, and 30 ton ha-1. The variables measures were plant height, leaf number, number of tillers, total chlorophyll content and fresh weight of rhizomes. The results of the study showed that the interaction between giving leaf fertilizer green tonic and organic fertilizer had no significant effect on all the variables of the growth and yield of red ginger (plant height, leaf number, number of tillers, total chlorophyll content and fresh weight of rhizomes), however the real effects occurred in each treatment of a single factor. Leaf fertilizer Green Tonic had significant effect on all variables of the growth and yield of red ginger were observed. All concentration of leaf green tonic was tested 4, 5, 6 ml l-1 of water showed the growth and yield of red ginger were good, indicated by yield of fresh weight rhizome were highest at a concentration of 6 ml liter-1 of water with the weight of fresh weight of rhizome amounted to 104.24 g and significantly different from the control that is 74.93 g. Organic fertilizeronly had significant effect on plant height, leaf number, number of tillers, however it had not significant effect on the growth and yield of red ginger variables such as fresh weight of rhizome and total chlorophyl content. All doses of organic fertilizerwere given 10, 20, and 30 to ha-1 showed the good growth of plant height, the highest plant height at a dose of 30ton ha-1 is 67.08 cm and were significantly different from the control at 57.42 cm. Keywords: green tonic, chicken manure, red ginger, and peatland soil.